2018
DOI: 10.1186/s12882-018-1019-x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids pulse therapy and oral corticosteroids therapy for IgA nephropathy patients with advanced chronic kidney disease: results of a multicenter, large-scale, long-term observational cohort study

Abstract: BackgroundCorticosteroids are widely used to reduce the urine protein levels of patients with immunoglobulin A nephropathy (IgAN). However, their potential preventive effects on end-stage kidney disease (ESKD) are unclear.MethodsWe previously performed a large-scale, long-term multicenter cohort study of patients with biopsy-proven IgAN treated between 1981 and 2013 (n = 1923). Based on the results, we reported that corticosteroids pulse therapy was potentially effective for the treatment of patients with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…PharmOmics dose/time-segregated (64% AUC, p=0.001) and meta databases (61% AUC, p=0.028) both showed a significant performance ( Figure 8D ), whereas from the other tools evaluated only CMAP (63% AUC, p<0.001) showed a significant performance (L1000 43% and CREEDS 56% AUC, non-significant). The top 5 nephrotoxic drugs predicted by PharmOmics were dexamethasone (potential CKD alleviating agent) (57,58), naproxen (documented nephrotoxic drug in DrugBank), cholecalciferol (potential CKD alleviating agent) (59), beta-estradiol (potential alleviating agent in women) (60,61), and ibuprofen (documented nephrotoxic drug in DrugBank). We also examined the gene overlap patterns of the top drugs with the CKD gene network ( Figure 8E ) and found sparse overlap, which again is in contrast to the top hepatotoxicity drugs ( Figure 7E ).…”
Section: Resultsmentioning
confidence: 99%
“…PharmOmics dose/time-segregated (64% AUC, p=0.001) and meta databases (61% AUC, p=0.028) both showed a significant performance ( Figure 8D ), whereas from the other tools evaluated only CMAP (63% AUC, p<0.001) showed a significant performance (L1000 43% and CREEDS 56% AUC, non-significant). The top 5 nephrotoxic drugs predicted by PharmOmics were dexamethasone (potential CKD alleviating agent) (57,58), naproxen (documented nephrotoxic drug in DrugBank), cholecalciferol (potential CKD alleviating agent) (59), beta-estradiol (potential alleviating agent in women) (60,61), and ibuprofen (documented nephrotoxic drug in DrugBank). We also examined the gene overlap patterns of the top drugs with the CKD gene network ( Figure 8E ) and found sparse overlap, which again is in contrast to the top hepatotoxicity drugs ( Figure 7E ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the risk of ESKD within 6 years was significantly reduced, which seems to support an association between long-term renal outcomes and proteinuria in IgAN patients. In addition, a multicenter, large-scale, long-term follow-up observational c o h o r t s t u d y s h o w e d t h a t i m m u n o s u p p r e s s a n t / corticosteroid treatment in IgAN patients had better longterm renal outcomes (29). Meanwhile, a 15-year follow-up study of 1,243 children with IgAN in China showed that immunosuppressant/corticosteroid therapy improved longterm renal outcomes (30).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of corticosteroid on various infectious diseases, including viral infections such as Epstein-Barr virus infection and infectious croup as well as severe bacterial infections such as tuberculous meningitis and typhoid fever, are well known. Furthermore, methylprednisolone pulse therapy (30 mg/kg/day or 1 g/day for adults) is used for 3 or more consecutive days for severe infectious disease and immune-mediated diseases such as MP pneumonia, lupus nephritis, KD, acute central nervous system diseases, and even advanced chronic kidney diseases [ 117 , 118 ], although the diseases are rare in older individuals. During this pandemic, some organ transplant recipients treated with T-cell suppressants seem to be protected from pneumonia [ 119 ], and older patients receiving anticancer drugs can recover from severe COVID-19 [ 120 ].…”
Section: Treatmentmentioning
confidence: 99%